Is Chinese Competition Causing Deindustrialization in Brazil?. (November 2015) - Jenkins, Rhys
There has been a lively debate in Brazil in recent years, involving sectors of business, the labor movement, and academics, over deindustrialization and the future of the manufacturing sector. This is often linked to the growing relation between Brazil and China, which is now the country's most significant trade partner. Brazil has experienced relative deindustrialization in the sense of a declining share of the manufacturing sector in gross domestic product that is mainly attributable to the changes in the country's trade balance in manufactures. The direct and indirect impacts of China on Brazilian manufacturing have contributed to this relative deindustrialization and the "primarization" of Brazilian exports through competition in the domestic market and in exports. Nos últimos anos, instaurou-se no Brasil um debate acirrado entre empresários, acadêmicos e sindicalistas sobre a desindutrialização e o futuro do setor manufatureiro. O fenômeno é frequentemente associado aos crescentes laços entre Brasil e China, hoje o mais importante parceiro comercial do país. O Brasil vem passando por uma relativa desindustrialização devida ao intenso declínio da participação do setor de transformação no Produto Interno Bruto. Atribui-se essa queda às mundanças provocadas pelos resultados da manufatura na balança comercial. Os impactos diretos e indiretos exercidos pela China sobre o setor secundário brasileiro têm contribuido para essa relativa desindustrialização, assim como para a primarização das exportações brasileiras por meio da competição no mercado doméstico e nas exportações.